Organizing across cognitive asymmetry in human–AI collaboration: A study of perfume creation - Yokoi, Tomoko; Martinez, Daniella Laureiro; Magni, Federico; Brusoni, Stefano (Strategic Management Journal, 2026)
Abstract Research Summary As organizations increasingly adopt generative AI (GenAI), they face a strategic challenge: not only deciding which tasks AI should perform, but also how to organize the integration of human and AI efforts to produce viable solutions. We propose that a cognitive asymmetry between human's tacit, embodied knowledge and AI's codified knowledge creates a representational gap that complicates human–GenAI collaboration. Through a qualitative study of professional perfume creation, we identify representational integration as an organizing process through which humans and GenAI coordinate to bridge this gap. This process unfolds across three practices: allocating tasks based on cognitive advantages, converting knowledge across tacit and codified forms, and steering GenAI outputs as problem solving evolves. This study advances a novel organizing perspective on human–GenAI collaboration under conditions of cognitive asymmetry. Managerial Summary Organizations increasingly deploy GenAI in knowledge‐intensive work, yet many struggle to convert human and AI contributions into strategic value. This study takes a cognitive lens, showing that humans and GenAI rely on different forms of cognition—and that value emerges when organizations can coordinate and combine them. Successful human–GenAI collaboration therefore requires more than adopting powerful models. It depends on organizing practices that help employees translate across representational formats, relate GenAI outputs to embodied expertise, and iteratively steer GenAI as their interpretations evolve. Investing in these practices and skills allows organizations to harness GenAI's generativity while recognizing that human sensemaking, tacit knowledge, and contextual understanding remain indispensable for producing coherent, high‐quality outcomes.